Phase relations in the Nd2O3-Fe2O3 system: Structure and magnetic properties of perovskite NdFeO3 ceramics - Vedel Dmytro V.; Stasyuk Oleksandr O.; Samelyuk Anatoly V.; Aguirre Myriam H. (Processing and Application of Ceramics)
The phase relations in the Nd2O3-Fe2O3 system at 1300 and 1400 °C were studied in the whole concentration range by X-ray diffraction (XRD) and scanning electron microscopy (SEM). The isothermal cross-sections of the Nd2O3-Fe2O3 phase diagram at 1300 and 1400 °C are characterized by the presence of three singlephase (A-Nd2O3, NdFeO3, Fe2O3) and two two-phase (A-Nd2O3 + NdFeO3, NdFeO3 + Fe2O3) regions. The composition corresponding to the perovskite phase is 51mol% Nd2O3 - 49mol% Fe2O3. In the next step, the investigation was focused on this composition. Nanocrystalline NdFeO3 powders with perovskite structure were obtained by the Pechini method and heterogeneous precipitation from nitrate solutions. The influence of the production method on the microstructure, morphology and magnetic properties of the NdFeO3 nanopowders was studied. According to XRD, SEM and TEM, the synthesized perovskite NdFeO3 is single-phase with a particle size of 60-90 nm. The morphology of powder particles primarily depends on the synthesis method. The powder showed ferromagnetic behaviour and had saturation magnetization 0.8 and 0.81 emu/g.